Relación entre rasgos de personalidad y el síndrome de burnout en empleados de diferentes sectores: revisión aplicada - Benvenuto Montenegro, Viviana (2023)
Burnout Syndrome (BS) is one of the main causes of the deterioration of workforce health, as well as great economic losses for organizations. Although research suggests that the development about this labor phenomenon is due to situational factors related to the work environment, various authors point that we should not ignore individual differences. The main goal of the study is to identify the relationship between personality traits and BS in employees from different sectors. Following the indicators of the PRISMA guide, we consulted the databases Scopus, Web of Science and SciELO, were chosen for the analysis 10 studies that evaluated both variables and fulfill the inclusion and exclusion criteria. It was concluded that there is a significant relationship between personality traits and BS, evidenced by the differences found in the same labor environment. Neuroticism’s trait is the trait with the highest prediction of BS. The traits of extraversion, conscientiousness, kindness and openness have a positive and negative relationship with BS, and it is recommended that they should not be interpreted without considering other variables.